The Agatha Christie hour. Set 2 [videorecording (DVD)] - Frankau, John; Sandys, Pat; Bates, Ralph, 1940-1991; Kermode, Robin, 1958-; Cazenove, Christopher; Christie, Agatha, 1890-1976 (Distributed by Acorn Media, 2010)
Dame Agatha left us more than Marple and Poirot. Set in Art Deco England, these classic stories spotlight lesser-known Christie sleuths solving crimes of the heart as well as larceny and murder.